1991
DOI: 10.1172/jci115101
|View full text |Cite
|
Sign up to set email alerts
|

Guanine ribonucleotide depletion inhibits T cell activation. Mechanism of action of the immunosuppressive drug mizoribine.

Abstract: The immunosuppressive drug, mizoribine, has been used to prevent rejection of organ allografts in humans and in animal models. Based on studies in cell lines, mizoribine has been postulated to be an inhibitor of inosine monophosphate (IMP) dehydrogenase (EC1.2.1.14), a pivotal enzyme in the formation of guanine ribonucleotides from IMP. To further characterize the mechanism of action of this drug, we studied the effect of mizoribine on human peripheral blood T cells stimulated with alloantigen, anti-CD3 MAb, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(74 citation statements)
references
References 40 publications
5
67
0
Order By: Relevance
“…results in the depletion of the intracellular guanine nucleotide. The depletion of the guanine nucleotide causes G i/s blockage in human T cells (12). Although immunophilins have been investigated for immunosuppressants cyclosporin A, FK506, rapamycin, and deoxyspergualin, immunophilin specific for mizoribine has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…results in the depletion of the intracellular guanine nucleotide. The depletion of the guanine nucleotide causes G i/s blockage in human T cells (12). Although immunophilins have been investigated for immunosuppressants cyclosporin A, FK506, rapamycin, and deoxyspergualin, immunophilin specific for mizoribine has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of the immunosuppressive effects of mizoribine demonstrated that mizoribine is phosphorylated by adenosine kinase (10), and the monophosphate inhibits from IMP dehydrogenase (10) or both IMP dehydrogenase and GMP synthase (11). The inhibition of the enzymes results in the depletion of intracellular guanine nucleotides as shown in both murine and human systems (12).…”
mentioning
confidence: 99%
“…This enzyme is strongly expressed in activated T and B cells (11). The antiproliferative effect of mycophenolate acid on T cells was clearly demonstrated in vitro (7,8,12,13). Methotrexate (MTX) is a folate antagonist that blocks dihydrofolate reductase and TS (14), but it can also block the first step of purine biosynthesis (15).…”
Section: Restriction Of De Novo Nucleotide Biosynthesis Interferes Wimentioning
confidence: 99%
“…Downregulation of the CDK inhibitor p27 Kip1 was shown to depend on the binding of IL-2 to its high-affinity trimeric receptor (11)(12)(13). Earlier studies with the immunosuppressive agent mizoribine (MZB), another inhibitor of IMPDH, have shown that depletion of guanine nucleotides in T lymphocytes inhibits the entry into S phase of the cell cycle, but does not alter early G 1 events such as expression of c-Myc, IL-2, or IL-2R (14). Therefore, we investigated whether IMPDH inhibitors, including MPA, could affect T cell proliferation by interfering with IL-2-dependent signaling events that are required for p27 Kip1 degradation and progression to the S phase of the cell cycle.…”
Section: Ycophenolate Mofetil (Mmf)mentioning
confidence: 99%